2001
DOI: 10.2307/2657135
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenetic analysis of Prunus and the Amygdaloideae (Rosaceae) using ITS sequences of nuclear ribosomal DNA

Abstract: The economically important plum or cherry genus (PRUNUS:) and the subfamily Amygdaloideae of the Rosaceae have a controversial taxonomic history due to the lack of a phylogenetic framework. Phylogenetic analysis using the ITS sequences of nuclear ribosomal DNA (nrDNA) was conducted to construct the evolutionary history and evaluate the historical classifications of PRUNUS: and the Amygdaloideae. The analyses suggest two major groups within the Amygdaloideae: (1) PRUNUS: s.l. (sensu lato) and MADDENIA:, and (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
136
1
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(159 citation statements)
references
References 43 publications
(44 reference statements)
17
136
1
5
Order By: Relevance
“…It represents an important economical resource because many species produce edible fruits (e.g. plums, peaches, apricots, cherries and almonds), oil, wood and some species are employed as ornamental plants [2].…”
Section: Introductionmentioning
confidence: 99%
“…It represents an important economical resource because many species produce edible fruits (e.g. plums, peaches, apricots, cherries and almonds), oil, wood and some species are employed as ornamental plants [2].…”
Section: Introductionmentioning
confidence: 99%
“…-Prunus consists of c. 200 species growing mostly in the temperate parts of the Northern Hemisphere, but with many representatives in tropical and subtropical regions (e.g. Yü et al 1986;Lee & Wen 2001;Gu & Bartholomew 2003;Mabberley 2008). Native Prunus shrubs and trees in China and East Asia thrive at elevations between 200-3800 m a.s.l.…”
mentioning
confidence: 99%
“…Guo et al (1992) showed that Amygdalus persica has also compound bud in one axil and these buds have the same composition as those in A. mume, which was revealed by this study. Phylogenic analysis based on ITS sequences of ribosomal DNA showed that Armeniaca mume and Amygdalus persica were closely related to each other (Lee and Wen 2001), and there is a taxonomic remark that the genus Armeniaca and Amygdalus could be included into Prunus s. s. (Ohba 1992). The analysis and remark are supported by the result obtained from the morphological analysis in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Prunus s. l. (Rehder 1940) includes some species which have two or three buds in one axil (Ohba 1989), and this multiplicity may be a trait reflecting phylogenic relationships in Prunus s. l. (Lee and Wen 2001;Iwamoto et al 2001).…”
Section: Introductionmentioning
confidence: 99%